2008
DOI: 10.1038/sj.bjc.6604228
|View full text |Cite
|
Sign up to set email alerts
|

Risk for contralateral breast cancer among carriers of the CHEK2*1100delC mutation in the WECARE Study

Abstract: The protein encoded by the CHEK2 gene is involved in cellular repair of DNA damage. The truncating mutation, CHEK2*1100delC, seems to increase the risk for breast cancer. We investigated whether the CHEK2*1100delC mutation carrier status increases the risk for asynchronous contralateral breast cancer (CBC) and whether it interacts with radiation therapy (RT) or chemotherapy in regard to CBC risk. The germline mutation frequency was assessed in 708 women with CBC and 1395 women with unilateral breast cancer (UB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
25
3
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 20 publications
(32 reference statements)
3
25
3
1
Order By: Relevance
“…5,[13][14][15][16][17][18][19] For homozygous carriers, our observations indicate that (contralateral) breast cancer risk may be as high as to justify preventive mastectomy (or at least intensified screening), but longitudinal studies on more cases are needed to arrive at more accurate risk estimates.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…5,[13][14][15][16][17][18][19] For homozygous carriers, our observations indicate that (contralateral) breast cancer risk may be as high as to justify preventive mastectomy (or at least intensified screening), but longitudinal studies on more cases are needed to arrive at more accurate risk estimates.…”
Section: Discussionmentioning
confidence: 93%
“…One study has reported an increased contralateral breast cancer risk when heterozygous patients had received radiotherapy as part of the treatment for their first breast tumor; another reported a similar but not statistically significant tendency. 15,19 Genotyping of larger cohorts is needed to better understand the effect of different treatments on breast cancer patients carrying the 1100delC allele. In the future, this can lead to personalized treatment strategies for 1100delC heterozygous and homozygous patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The risk is particularly high in women with rare high-penetrance sequence variants, such as mutations in BRCA1 or BRCA2, where the 10-year risk may approach 25% to 30% (4,5). Mutations in CHEK2 also increase the risk of CBC, albeit to a lesser degree (6,7), and rare pathogenic PALB2 mutations have also been shown to increase the risk of CBC (8,9). In some family studies and within subgroups of breast cancer patients, rare mutations in the ATM gene have also been shown to increase the risk of CBC (10,11).…”
mentioning
confidence: 99%